1998
DOI: 10.1021/ja980147e
|View full text |Cite
|
Sign up to set email alerts
|

Aliphatic/Aromatic Amino Acid Pairings for Polyamide Recognition in the Minor Groove of DNA

Abstract: Selective placement of an aliphatic β-alanine (β) residue paired side-by-side with either a pyrrole (Py) or imidazole (Im) aromatic amino acid is found to compensate for sequence composition effects for recognition of the minor groove of DNA by hairpin pyrrole−imidazole polyamides. A series of polyamides were prepared which contain pyrrole and imidazole aromatic amino acids, as well as γ-aminobutyric acid (γ) “turn” and β-alanine “spring” aliphatic amino acid residues. The binding affinities and specificities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
119
2
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 134 publications
(123 citation statements)
references
References 45 publications
1
119
2
1
Order By: Relevance
“…needed to reset the register for the following (C-terminal) residue. 21 It appears that the b residue is necessary for the two flanking Im residues in Im -b-Im to orient properly in order to form hydrogen bonds. The Im -b-Py subunit forms only one Im·G hydrogen bond, and therefore the flexibility is not as critical.…”
Section: The Importance Of B-alaninementioning
confidence: 99%
See 1 more Smart Citation
“…needed to reset the register for the following (C-terminal) residue. 21 It appears that the b residue is necessary for the two flanking Im residues in Im -b-Im to orient properly in order to form hydrogen bonds. The Im -b-Py subunit forms only one Im·G hydrogen bond, and therefore the flexibility is not as critical.…”
Section: The Importance Of B-alaninementioning
confidence: 99%
“…The aliphatic amino acid b-alanine (b), previously used to relax the over-curvature of long contiguous aromatic subunits, 18 -20 was incorporated between imidazole groups as Im -b-Im to target 5 0 -GNG-3 0 successfully. 21 In a breakthrough report, the 1:1 motif was revived by Laemmli and co-workers and used to effect phenotypic changes in Drosophila melanogaster by binding to 5 0 -GAGAA-3 0 repeats in satellite regions of the fly genome. 22 In the Laemmli design, b-alanine residues were used to add flexibility between ring subunits, allowing the Im residues to register optimally with the DNA helix.…”
Section: Introductionmentioning
confidence: 99%
“…Sequence-specific DNA recognition depends on side-byside pairing of pyrrole (Py) 1 and imidazole (Im) amino acids; a Py opposite an Im targets a C⅐G base pair, and an Im opposite a Py targets a G⅐C base pair (1,2). Py/Py, Py/␤-alanine (␤), and ␤/␤ pairs binds both A⅐T and T⅐A base pairs (2,3). Recent studies have shown that A/T degeneracy can be overcome by replacing one pyrrole ring of the Py/Py combination with 3-hydroxypyrrole (Hp), with the result that the Hp/Py prefers T⅐A over A⅐T base pairs (4).…”
mentioning
confidence: 99%
“…Various types of sequencespecific Py-Im polyamides have been developed to control gene expression by competitive binding against DNA-binding proteins such as transcription factor. [7][8][9][10][11][12][13][14][15][16][17][18] The introduction of a -alanine moiety within the hairpin motif allows the crescent-shaped Py-Im polyamides to fit into the minor groove of dsDNA, and antiparallel pairings of /, Py/-pair recognize both T-A and A-T. 19 In general, the -linker was set in the hairpin motif to extend the DNA sequence recognition. Although long hairpin Py-Im polyamides have interesting biological properties, they tend to  Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…Polyamide 1 is a standard design with one -alanine inserted within the structure to relax the distortion between three rings. 19 Polyamides 2 and 3 each has one AO unit in either the N-or C-side strand, respectively. Notably, the introduction of the AO unit can decrease the number of coupling steps because the moiety covers two base pairs.…”
Section: Introductionmentioning
confidence: 99%